REVIEW OF "MUSIC THEORY" - Abdurakhmanova Manzura Batirovna (Galaxy International Interdisciplinary Research Journal, 2021)
Music education is a part of the educational process and the solution of new pedagogical problems is actively involved. Orientation to new goals of education requires not only changing the content of the studied subjects but also the methods and forms of organizing the educational process, enhancing the activities of students during the lesson, bringing the topics under study closer to real life and looking for ways to solve emerging problems.